Addressing dental workforce challenges at the state level through financial incentives, educational innovation, and teledentistry initiatives - Eli Schwarz; Jonathan P. Mcelfresh; Alexandra Dest; Richie Kohli (BMC Oral Health)
Abstract Background To address access to dental care and oral health inequity issues comprehensively this project aimed to 1) develop, test and demonstrate a community-based recruitment of oral health workforce capacity in severely underserved areas of Oregon, 2) develop a retention toolkit with the potential to increase the longevity of providers in Dental Health Professional Shortage Areas (DHPSAs), 3) expand the pipeline of oral health professionals willing to practice in rural underserved counties of Oregon through experiential learning, and 4) demonstrate that a teledentistry model would be applicable in severely underserved areas. Methods Administrative changes to state loan repayment initiatives were used to leverage recruitment efforts of dental workforce to DHPSAs. Senior dental students on community-based rotations were surveyed about what factors were important to them in choosing a practice location and what their preferred location of practice was after graduation. Counties severely underserved by dental care services were offered teledentistry-supported dental care in community health centers within the framework of the virtual dental home model. Results Both dentists (n = 62, 80.5%) and expanded practice dental hygienists (n = 15, 19.5%) were recipients of the state loan repayment awards. Of 117 senior dental students 57 responded (49%) to the survey. The factors of greatest importance for their practice choice were clinic characteristics, clinic and community support, geographic location, and future opportunities with some gender differences. Clinical oral health care in counties without dental clinics was provided in collaborating community health centers supported by teledentistry led by expanded practice dental hygienists. Conclusion The combined efforts of the state, dental education, local administrators and clinicians can be successful in addressing the complex problem of access to and utilization of dental care and providing oral health care to underserved populations. Innovative financial, educational, clinical, administrative and human resource methods must be used collaboratively to induce dental graduates to choose practice locations outside of major urban centers and retain their longevity.